Anniversary Padilla Louis and Elinora Padilla (Raton, New Mexico Raton Range, 1997)
Newspaper Article on the 50th Anniversary of Louis and Elinora Padilla
Master list item #: 4
File location is in the Raton File Cabinet
Keywords: Padilla, Louis; Padilla, Elinora; Vance, James L; Alderette, Tom; Sandoval, Gene; Sandoval, Eva; Padilla, Pat; Padilla, Jonallyn; Padilla, Richard; Padilla, Darla; Padilla, Michael; Padilla, Alex; Audrey; Padilla, Gilbert; Tina; Vigil, Irene; Vigil, Arnie; Cardenas, Frances; Cardenas, Richard; Martinez, Virginia; Martinez, David; Smith, Carman Padilla; Padilla, Anna; Tim; Castillo, Julie Padilla; Gilbert; St. Patrick's St. Joseph's parish; History -- Raton, New Mexico; Biography; Local History; Life and Customs; Anniversary; Celebration; Marriage; Raton, New Mexico; Las Vegas, New Mexico